Using systematic synthetic phonics as an approach for early literacy: The case of rural indigenous children / Yap Jia Rong - Yap, Jia Rong (2014)

(untitled)
The majority of empirical research into systematic phonics was focused on native speakers of the English Language. Little evidence has been collected to prove its effectiveness with audiences who are English Language Learners (ELL). The purpose of this quantitative randomized comparison experimental study was to determine if systematic synthetic phonics (SSP) instruction records a better improvement than the KSSR phonics in the reading fluency and spelling ability of Year-2 primary school children of the indigenous tribe from the rural parts in Sarawak, Malaysia. Five instruments, (1) productive letter-sound test (PLST), (2) free-sound isolation test (FSIT), (3) reading test (RT), (4) spelling test (ST) and (5) oral-reading fluency test (ORFT) were administered to measure phonemic awareness, decoding, reading and spelling ability. Data were collected from pretest, immediate posttest and 3-week lapsed posttest. The participants in the experimental and control groups received 40 sessions of SSP and KSSR phonics training respectively. Both conditions used synthetic phonics. The SSP training was done in phases and stages, whilst the KSSR phonics training adhered to the practices specified in the ‘Standard Document’ and pupil’s textbook. The results demonstrated that both groups recorded significant improvement in reading and spelling, but children’s performance in the experimental group surpassed the control group significantly. Thus, the strategy of systematic synthetic phonics should be implemented in classrooms to help develop children’s early reading fluency and spelling ability.